NILAI TAMBAH SNACK SAYURAN ORGANIK UD JIBARIZ DI KECAMATAN GETASAN KABUPATEN SEMARANG - Maria Mega Mawarni; Maria Maria (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2021)
Home industry Jibariz is one of the SMEs that processes organic vegetable products into sticks and dumplings. The purpose of the study was to determine the amount of added value generated, analyze costs, revenues, profits from processing, and business developments from the trend of selling Jibariz organic vegetable snacks 2 years before (2018, 2019) and during the Covid-19 pandemic (2020). This research was conducted in Jampelan hamlet, Getasan sub-district, Semarang district. Sampling was done intentionally (purposive sampling). The data was processed using quantitative descriptive methods. Analysis of the data used in this study is the analysis of added value using the Hayami method. The result of the research shows that the added value of Jibariz organic vegetable snack is Rp. 61,800 per kilogram or 68.66% of the product value. The average cost incurred each month is Rp. 3,557,556 with a total production of 600 packs per month and able to provide a monthly income of Rp. 9,000,000 and the profit earned is Rp. 3,181,000. The value of the R/C ratio obtained is 1.5 so it is feasible to continue. The development of Jibariz's organic vegetable snack business in the 2 years before Covid-19 the sales trend fell, while in 2020 during the Covid-19 pandemic the sales trend increased.